2018
DOI: 10.1177/0892705718799816
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and sensitivity analysis of drilling parameters for sustainable machining of carbon fiber–reinforced polypropylene composites

Abstract: Machining processes face two major challenges: sustainability and cleaner production. However, the effective utilization of tool and methods of lubrication system in sustainable machining have been dealt in depth in earlier investigations. This work aims to optimize sustainable machining parameters in drilling process for recyclable carbon fiber-reinforced polypropylene (CFR-PP) composites. This work is focused on modeling and optimization of drilling parameters for sustainable machining with respect to thrust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
0
9
0
1
Order By: Relevance
“…They found that the weights used in the multi-objective optimization process influence the prediction variance. Mudhukrishnan et al [ 28 ] optimized drilling parameters, such as spindle speed, feed and drill material, with respect to thrust force and torque, and performed a sensitivity analysis to assess the impact of control variables on the responses.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the weights used in the multi-objective optimization process influence the prediction variance. Mudhukrishnan et al [ 28 ] optimized drilling parameters, such as spindle speed, feed and drill material, with respect to thrust force and torque, and performed a sensitivity analysis to assess the impact of control variables on the responses.…”
Section: Introductionmentioning
confidence: 99%
“…1−3 They are fantastic tools to strengthen any study dealing with varying parameters, as they allow weight to be given to all observations and trends in order to enable the pinpointing of optimal conditions. DoE have been used extensively in a very wide range of fields, from mechanical engineering 4,5 to numerical simulations. 2 The pharmaceutical, 6 medical, 7 and chemical engineering 8−12 fields also make broad use of DoE in their research.…”
Section: ■ Introductionmentioning
confidence: 99%
“…DoE have been used extensively in a very wide range of fields, from mechanical engineering , to numerical simulations . The pharmaceutical, medical, and chemical engineering fields also make broad use of DoE in their research.…”
Section: Introductionmentioning
confidence: 99%
“…Entre otras, un inconveniente crítico de estas fibras está relacionado a los costos y condiciones de producción como, por ejemplo, que las CF requieren temperaturas extremadamente altas para obtener fibras altamente purificadas. Por otra parte, estas fibras de refuerzo convencionales tienen un impacto ambiental importante, relacionado a las etapas de producción y la problemática luego de su vida útil; esto significa que su producción en masa es prácticamente inviable [10,11].…”
Section: Introductionunclassified